A designed self-microemulsion delivery system for dihydromyricetin and its dietary intervention effect on high-fat-diet fed mice. (1st October 2022) - Lyu, Qiyan; Chen, Lei; Lin, Shiye; Cao, Hui; Teng, Hui
Highlights: TPGS-QS-SMEDDS is designed to enhance the absorptivity of DMY. The DMY-S can regulate the increase of body weight, serum and hepatic TG. The DMY-S can decrease the ratio of Firmicutes to Bacteroidetes . The DMY-S could inhibit sphingomyelin, CoA, nicotinate acid, and pyruvate expressions. Abstract: The present study aims to design a self-microemulsion delivery system (d-α-tocopheryl polyethylene glycol 1000 succinate - quillaja saponin) to enhance the absorptivity of dihydromyricetin (DMY-S), and to investigate its dietary intervention effect on high-fat-diet (HFD) fed mice. We find DMY-S can inhibit the increase of body weight and fat mass, preventing non-alcoholic fatty liver disease. Compared to the model group, the abundance of mice intestinal flora is mainly changed in certain bacterial genera of Firmicutes and Bacteroides, including norank_f_Muribaculaceae and Blautia. The result of metabolism analysis indicated that the expression levels of cincassiol B, creatine, pantothenic acid and aminobutyric acid in the liver tissues of mice treated with DMY-S showed a down-regulation. The DMY-S prevented hyperlipidemia in HFD mice mainly by affecting different pathways including glycerophospholipid metabolism, sphingolipid metabolism and pantothenate and CoA biosynthesis.